2014
DOI: 10.1007/s00423-014-1238-y
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic liver resection: a comparative study from a single center

Abstract: Robotic liver resection is a safe and feasible option for liver resection in experienced hands. The authors suggest that since the robotic surgical system provides sophisticated advantages, the retrenchment of medical cost for the robotic system in addition to refining its liver transection tool may substantially increase its application in clinical practice in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 19 publications
2
90
0
Order By: Relevance
“…Robotic MIS hepatectomy as a field is moving past its infancy. Nota et al (12) recently reported a collected series analysis of the 12 best studies up to 2015 (7,8,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). There is no doubt that hemi-hepatectomies can be performed with safety by the robotically-assisted approach (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Robotic MIS hepatectomy as a field is moving past its infancy. Nota et al (12) recently reported a collected series analysis of the 12 best studies up to 2015 (7,8,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). There is no doubt that hemi-hepatectomies can be performed with safety by the robotically-assisted approach (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Only in the series of major hepatectomies, a mean operative time ranged from 229.4 to 621 min [27][28][29], and the estimated blood loss was from 200 to 478 mL [24][25][26], a conversion to open rate was 3.7-7% , a morbidity rate 7.1-40% [26][27][28][29], a null mortality rate and R0 resection rate of 100% were reported except for the series of Lai et al [29]. In conclusion, the postoperative results in case of major hepatectomies are similar for robotic and laparoscopic approaches, underlying the safety of the robotic technique.…”
Section: Discussionmentioning
confidence: 99%
“…Most data were obtained from prospectively maintained databases. Tables 3 and 4 showed the results of nonrandomized comparative studies comparing robotic and laparoscopic partial hepatectomy in patients with minor hepatectomies [18][19][20][21][22][23][24][25] and in patients with minor and major hepatectomies [26][27][28][29] . Although the perioperative outcomes seemed to be similar in both groups, the benefit of robotic approach has been shown in several studies.…”
Section: Robotic Vs Conventional Laparoscopic Partial Hepatectomymentioning
confidence: 99%